If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 4 = 5 + -1y Reorder the terms: 4 + 3y = 5 + -1y Solving 4 + 3y = 5 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 4 + 3y + y = 5 + -1y + y Combine like terms: 3y + y = 4y 4 + 4y = 5 + -1y + y Combine like terms: -1y + y = 0 4 + 4y = 5 + 0 4 + 4y = 5 Add '-4' to each side of the equation. 4 + -4 + 4y = 5 + -4 Combine like terms: 4 + -4 = 0 0 + 4y = 5 + -4 4y = 5 + -4 Combine like terms: 5 + -4 = 1 4y = 1 Divide each side by '4'. y = 0.25 Simplifying y = 0.25
| (X-3)(3-y)=0 | | .5x+.375x+x= | | 24*2x*x=72000 | | -2n-2=-2n-7 | | 12k=8 | | 3.4(x+3)=15.3 | | 12(x)=5(y) | | z^2-(1+2i)z+1+7i=0 | | 6(4-x)+6x=244 | | 299,792,000/x=0.50 | | 0.5x+2x=7 | | 7-6x=x-49 | | .5(3x-24)=9 | | 6x-(2x+7)=3+4(x-9) | | 2x+1=3+4x | | m^2+16m=-49 | | -8m-10+6m=36 | | 5x^2+18x+45=0 | | 5x+9=15-6 | | 1+8y=-32 | | X^2-4x-12y+16=0 | | 8+6x+3x=-10 | | 3k-15=78 | | 8(5n-4)+8=-264 | | 6c-64=80 | | Y/3-15=-6 | | -7m-5=37 | | 4m+70=-30 | | 8y+4(7+y)=3(y-2)+10 | | p(t)=(348)3t/4 | | 4+7x-5x=-6 | | W=2x+2y |